(untitled) (Al-Academy, 2021)
Dramatic wonders at children’s theatre shows Search summary The importance of the current study is to present an important concept, from the point of view of those interested in the field of literature and the theater of the child, namely (miraculous) because it represents an innate tendency immersed in the child’s mind, and therefore it is easy to impress him when attracting him with a text and a presentation addressed to him, to achieve the aesthetic and intellectual vision, so the problem of research was in the following question: (dramatic wonders in children’s theater performances) and the importance of research lies in the importance of the importance of the role of wonder for dramatic discourse in children’s theatre performances, and research benefits the workers In educational and cultural institutions to build a knowledge base for the new generation with the intention of educating them through visual, audio, critical and aesthetic taste. The researcher used the descriptive analytical approach in dealing with the research community in the analysis of a play with aesthetic and educational contents and values in the first chapter, and the second chapter is the framework of research from two researchers, the first research: the aesthetic of theatrical discourse: what is the aesthetics of the art of theater and its importance and objectives, and the second research: wonders and their work in the children’s theater: based on the functioning of the senses of hearing and sight and their connotations in the visual presentation presented to children to the result of the theoretical framework He absorbed the research procedures and then followed this investigation a brief conclusion of the results related to the concept of wonder for the drama of the theatrical presentation presented to children with aesthetic dimensions influential and attractive through the effectiveness of form and content, as well as recommendations, and proposals, as the researcher recommended the need to enhance the status of the children’s theater, provide a theatrical space, and employ it properly to achieve the desired goals in education, and instill educational values And intellectual, aesthetic. Followed by a list of sources and references used in the search and the search summary in English. Opening words: Wonderland, Drama, Children’s Theatre